Role of Neutrophil-to-Lymphocyte Ratio as a Diagnostic Marker in Acute Appendicitis - Malik, Huma; Chaudhry, Muhammad Amjad; Iqbal, Tooba; Riaz, Samra; Abbasi, Sunnia; Hussain Shah, Syed Khurrum (Biological and Clinical Sciences Research Journal, 2025)
Acute appendicitis is the most frequent abdominal surgical emergency worldwide. In Pakistan, where access to advanced imaging is limited in many healthcare settings, timely diagnosis remains challenging. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential inflammatory biomarker to assist in the diagnosis of acute appendicitis. Objective: To evaluate the diagnostic accuracy of the neutrophil-to-lymphocyte ratio in predicting histopathologically confirmed acute appendicitis in patients presenting with clinical suspicion. Methods: A prospective observational study was conducted of PIMS hospital in Pakistan from January 2, 2025, to April 2, 2025. A total of 85 patients who were presented with suspected acute appendicitis were included. Complete blood counts were performed at admission, and NLR values were calculated. Final diagnoses were confirmed via histopathology. Patients were categorized into confirmed appendicitis and normal appendix groups. Data were analyzed using SPSS v25.0; t-tests and ROC curve analyses were performed to assess diagnostic accuracy. Results: NLR was significantly higher in the appendicitis group (6.8 ± 2.9) compared to the normal appendix group (2.9 ± 1.3) (p< 0.001). A cut-off value of NLR >4.5 yielded a sensitivity of 86.2%, specificity of 80.0%, and a positive predictive value of 91.5%. The area under the ROC curve was 0.889, indicating high diagnostic accuracy. Conclusion: The neutrophil-to-lymphocyte ratio is a simple, inexpensive, and reliable diagnostic marker for acute appendicitis. Its use as an adjunct to clinical evaluation can improve diagnostic accuracy and reduce unnecessary surgeries, especially in resource-limited Pakistani healthcare settings.